2020
DOI: 10.12659/msm.920265
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis in Lung Cancer Cells by Viburnum grandiflorum via Mitochondrial Pathway

Abstract: Departmental sources Background:Lung cancer is one of the leading causes of mortality and morbidity. Viburnum grandiflorum is a medicinal herb known for its wide spectrum of pharmacological activities, but its anti-cancer properties against lung cancer cells have not been previously investigated. The present study elucidated the antitumor effect and associated mechanism of methanol extract of Viburnum grandiflorum extract (VGE) against lung cancer cells. Material/Methods:The viability of H1650, HCC827, and H12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Taking into account the composition of studied extract, it was shown that chlorogenic acid, the main identified phenolic constituent, and its microbial metabolites induced S-phase cell-cycle arrest and activated caspase-3 at 500-1000 µM concentrations in Caco-2 cells [29]. Recently, it was demonstrated that methanolic extract from V. grandiflorum induced apoptosis in lung cancer H1650 and H1299 cell lines [8]. The study revealed the molecular mechanism involved MMP loss, release of cytochrome c into the cytosol, reduction of the anti-apoptotic Mcl-1 protein level, and activation of caspase-3.…”
Section: Effect Of V Opulus On Intracellular Atp Level Mitochondrial Membrane Potential and Apoptosis Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the composition of studied extract, it was shown that chlorogenic acid, the main identified phenolic constituent, and its microbial metabolites induced S-phase cell-cycle arrest and activated caspase-3 at 500-1000 µM concentrations in Caco-2 cells [29]. Recently, it was demonstrated that methanolic extract from V. grandiflorum induced apoptosis in lung cancer H1650 and H1299 cell lines [8]. The study revealed the molecular mechanism involved MMP loss, release of cytochrome c into the cytosol, reduction of the anti-apoptotic Mcl-1 protein level, and activation of caspase-3.…”
Section: Effect Of V Opulus On Intracellular Atp Level Mitochondrial Membrane Potential and Apoptosis Inductionmentioning
confidence: 99%
“…Whereas the antioxidant potential of guelder rose constituents is well characterized, its biological activity on the cellular model is not known very well. There are few studies revealing its anticancer properties against different cell lines, yet they match cytotoxicity with down-regulation of the cellular antioxidant defense system, mitochondria collapse, and cellular death induction [4,[8][9][10][11][12]. Furthermore, even less data indicate the cytoprotective activity of V. opulus, especially in regard to diet-related chronic diseases generated by increased oxidative stress [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Inflow cytometric analyses that only employ propidium iodide (PI) labeling, apoptotic cells typically exhibit hypodiploidy [31]. Notably, a biological investigation demonstrates that anticancer activity effectively suppresses the growth of various cancer cells by producing a subG1 population and promoting apoptosis [32][33][34][35][36][37][38][39]. The reduced DNA content observed in sub-G0/G1 cells can be attributed, in part, to the depletion of fragmented chromatin, which is widely recognized as a characteristic feature of apoptosis [40].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inhibiting the proliferation and inducing apoptosis of lung cancer has become a feasible strategy for the treatment of lung cancer. A large number of studies have also found that mechanisms of many natural anticancer drugs against lung cancer are related to the regulation of different signaling pathways to inhibit the proliferation of lung cancer cells and induce the apoptosis of lung cancer cells ( Wang S. et al., 2019 ; Han et al., 2020 ; Hu et al., 2020 ). Therefore, we subsequently designed corresponding in vitro experiments in order to prove the prediction results of network pharmacology.…”
Section: Discussionmentioning
confidence: 99%